1999
DOI: 10.1007/s004200050332
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal protection, environmental hygiene and exposure to pesticides on the health of immigrant farm workers in a desert country

Abstract: AChE depletion was found to be negatively associated with the use of gloves, of work coveralls, and of a scarf to cover the nose and mouth and with the implementation of safety and hygiene procedures on the farm. AChE depletion was positively associated with the frequency of pesticide spraying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 13 publications
5
44
0
Order By: Relevance
“…Most previous studies of farmworkers or greenhouse workers have found some evidence of job-related deficits in neurobehavioral performance or increases in neurologic symptoms (Bazylewicz-Walczak et al 1999;Ciesielski et al 1994;Gomes et al 1999;McConnell et al 1994;Rohlman et al 2001;Rosenstock et al 1991;Wesseling et al 2002). However, the observed changes were often small, with some inconsistencies in the specific neurologic defects that were observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most previous studies of farmworkers or greenhouse workers have found some evidence of job-related deficits in neurobehavioral performance or increases in neurologic symptoms (Bazylewicz-Walczak et al 1999;Ciesielski et al 1994;Gomes et al 1999;McConnell et al 1994;Rohlman et al 2001;Rosenstock et al 1991;Wesseling et al 2002). However, the observed changes were often small, with some inconsistencies in the specific neurologic defects that were observed.…”
Section: Discussionmentioning
confidence: 95%
“…There was little relationship of farm work to other tests of cognitive (symbol digit latency), sensory (visual contrast sensitivity), or motor (grip strength) function. Some but not all other studies of farm work or pesticide exposure have reported deficits in symbol digit latency, along with deficits in digit span, vibrotactile threshold, tapping, Santa Ana, and postural sway (Gomes et al 1999;London et al 1997;McConnell et al 1994;Rosenstock et al 1991;Sack et al 1993;Savage et al 1988;Steenland et al 1994Steenland et al , 2000Stephens et al 1995;Stokes et al 1995;Wesseling et al 2002). Although these results are not completely consistent, it is noteworthy that no study has reported an exposure-related improvement in performance.…”
Section: Discussionmentioning
confidence: 98%
“…Some highly toxic and bioaccumulative pesticides have caused serious pollution of soil, air, water, sediment, and food, often being biomagnified through the food chain to affect the health of individual organisms at higher trophic levels (Gomes et al 1999). The use of chlorinated pesticides was formally phased out in China in 1983.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of exposure differ greatly between workers, depending on various determinants of exposure (16,(18)(19)(20). Performing field studies of occupational pesticide exposure in agriculture provides us with exposure measurements in real-life conditions of pesticide use.…”
Section: (Phomopsis Viticola) and Black Rot (Guingardia Bidwelli)mentioning
confidence: 99%